Rancang Bangun Aplikasi Uji Kompetensi Pada Lembaga Sertifikasi Profesi Manajemen Wirausaha Dan Produktivitas Merdeka - Muhammad Ridwan Bahar; Tan Amelia; Rudi Santoso (Jurnal Sistem Informasi Universitas Dinamika, 2018)
Lembaga Sertifikasi Profesi or so-called LSP is an implementing agency of competency assessment and certification of competencies that have obtained a license from Badan Nasional Sertifikasi Profesi. During this LSP Manajemen Wirausaha dan Produktivitas Merdeka activities such tasks manually. This means that all activities ranging from acc candidate registration, schedule a test, fill out the results, to provide certification is done unsystematically. As a result, the process of activity LSP Manajemen Wirausaha dan Produktivitas Merdeka was not doing systematically and integrated, so that the recorded data is not automatically linked to other sections, as well as related data acc not stored and arranged in neat. Related to the above problems, the solution can solve it is with in her application competency test there in can organize the data related to the implementation of the competency test, to facilitate the search of data, determining the schedule and assessor in charge of the implementation of the competency test and the test result data of competence so acc considered competent will get a certificate of competence. The process of application testing has produced results and suitability of hope, and fit for use. Based on testing that has been done, the applications have been successfully running the maintenance process participant data, recording schedules competency testing, record maintenance scheme/KUK, passing, scoring and reporting certificate examinees and the assessment results to the leadership.